Modeling the Effects of Agricultural Innovation and Biocapacity on Carbon Dioxide Emissions in an Agrarian-Based Economy: Evidence From the Dynamic ARDL Simulations - Ali, Aminu; Usman, Monday; Usman, Ojonugwa; Sarkodie, Samuel Asumadu (Frontiers in Energy Research, 2021)
In this paper, we modeled the effects of income, agricultural innovation, energy utilization, and biocapacity on Carbon dioxide (CO2) emissions. We tested the validity of the environmental Kuznets curve (EKC) hypothesis for Nigeria from 1981 to 2014. We applied the novel dynamic autoregressive distributed lag (ARDL) simulations to develop conceptual tools for policy formulation. The empirical results confirmed the EKC hypothesis and found that agricultural innovation and energy utilization have an escalation effect on CO2 emissions whereas income and biocapacity have long-run emission-reduction effects. The causality results found agricultural innovation attributable to CO2 emissions and observed that income drives energy demand. Income, biocapacity, and energy utilization are found to predict changes in CO2 emissions. These results are validated by the innovation accounting techniques—wherein 22.79% of agricultural innovation corresponds to 49.43% CO2 emissions—5.95% of biocapacity has 35.78% attributable CO2 emissions—and 1.61% of energy spurs CO2 emissions by 16.27%. The policy implication for this study is that energy efficiency, clean energy utilization and sustainable ecosystem recovery and management are the surest ways to combat climate change and its impacts.